Antecedents and Consequences of Alfagift Customer Satisfaction - Dzikry Ulyl Azmy; Ahmad Abel Faruq; Aang Curatman (Jurnal Manajemen, 2025)
The rapid growth of Indonesia’s retail industry has made shopping easier. Customer behavior driven by impulsive needs and wants is driving this expansion. The emergence of shopping apps further supports transactions, driving customer activity and propelling the expansion of the retail industry. This study to examine and assess the relation among service quality, information quality, system quality, customer satisfaction, and customer loyalty. The participants of this study were individuals who live in Cirebon City and Regency and used Alfagift. This research method uses purposive sampling with 200 respondents through distributing online questionnaires distributed to Alfagift users. Data analysis was analyzed using structural equation modeling (SEM) and partial least squares (PLS) methods through the SmartPLS version 4.0 application. This study reveals that service quality is devoid of a positive and significant effect on Alfagift user loyalty. Conversely, however, Information Quality and System Quality are demonstrated to possess a positive and significant influence on Alfagift User Satisfaction. This study also discovered that Alfagift user fulfillment has a positive and significant effect on customer loyalty. Furthermore, customer satisfaction acts as a mediator that positively and significantly affects the relation among service quality and customer loyalty. In different terms, increasing service quality doesn’t automatically raise customer loyalty in the absence of higher satisfaction, which ultimately contributes to increasing customer loyalty to the Alfagift application.